13C isotopic abundances in natural nutrients: a newly formulated test meal for non-invasive diagnosis of type 2 diabetes. (1st June 2017) - Ghosh, Chiranjit; Mandal, Santanu; Pal, Mithun; Mukhopadhyay, Prabuddha; Ghosh, Shibendu; Pradhan, Manik
Abstract: A new method to replace commercially prepared 13 C-labelled glucose with naturally available 13 C-enriched substrates could result in promotion of the clinical applicability of the isotopic breath test for detection of type 2 diabetes (T2D). Variation of the carbon-13 isotope in human breath depends on the 13 C enrichment in the diet taken by subjects. Here, we formulated a new test meal comprising naturally available 13 C-enriched foods and subsequently administered it to non-diabetic control (NDC) subjects and those with T2D. We found that the new test meal-derived 13 C enrichment of breath CO2 was significantly lower in T2D compared with NDC. Furthermore, from our observations T2D exhibited higher isotopic enrichment of oxygen-18 ( 18 O) in breath CO2 compared with NDC following ingestion of the new meal. We determined the optimal diagnostic cut-off values of 13 C (i.e. δ 13 C‰ = 7.5‰) and 18 O (i.e. δ 18 O‰ = 3.5‰) isotopes in breath CO2 for precise classification of T2D and NDC. Our new method involving the administration of naturally 13 C-abundant nutrients showed a typical diagnostic sensitivity and specificity of about 95%, suggesting a valid and potentially robust global method devoid of any synthetically manufactured commercial 13 C-enriched glucose which thus may serve as an alternative diagnostic tool for routine clinical applications.